Protocol for prognosticating PPD using EEG changes during labor pain by uterine contractions: a prospective cohort study in the first stage of labor - Yan Wang; Wan-Ying He; Chang’ an A. Zhan; Shi-Lei Pan; Wen Wu; Feng-Xian Li; Hong-Fei Zhang (BMC Pregnancy and Childbirth)
Abstract Background Lack of motivation and behavioral abnormalities are the hallmarks of postpartum depression (PPD). Severe uterine contractions during labor are pain triggers for psychiatric disorders, including PPD in women during the puerperium. Creating biomarkers to monitor PPD may help in its early detection and treatment. It has been suggested that uterine contraction-induced labor pain plays a role in the emergence of this syndrome. Therefore, abnormal electroencephalography (EEG) patterns during the first stage of labor may provide useful information. Here, we propose that aberrant EEG patterns caused by painful uterine contractions may be predictive markers for PPD. Methods This study is a single-centre prospective cohort planned for 331 parturients for vaginal delivery in the maternity ward of Zhujiang Hospital from 2022 to 2023. At baseline, online or paper-based questionnaires, including the Edinburgh Postnatal Depression Scale (EPDS) and demographic data, will be collected when the parturient is admitted to labor. EEG, electrocardiography (ECG) and electrohysterography (EHG) signals will be monitored and recorded during the first stage of labor in the ward. Follow-up will be taken at the postpartum timepoints of day 3, day 42, and 3, 6 and 12 months, respectively. Power spectral density and functional connections will be quantified. The connections between PPD severity and EEG measurements as a function of time will be assessed using linear mixed-effects models. Maternal age, parity, and whether oxytocin is used during labor, all have an impact on the incidence of PPD, hence a stratified analysis will be carried out. Discussion We expect EEG changes caused by painful uterine contractions in the first labor may predict early PPD. The results from this study may act as a predictor for the development of PPD which may enhance long-term quality of life for the parturient and her offspring. Trial registration. Name of registry: EEG Alterations of Uterine Contractions in the First Stage of Labor Predicting PPD. Trial registration number: NCT05217251; registration date on the ClinicalTrial.gov platform: February, 1/2022.